Nathalie Bouzaglo. "Ficción adulterada. Pasiones ilícitas del entresiglo venezolano".Rosario: Beatriz Viterbo Editora, 2016. 224 pp. - Saraceni, Gina; Pontificia Universidad Javeriana, Bogotá, COLOMBIA (2017)
null